Pengembangan LKPD Canva Berbasis Etnomatematika Getuk untuk Meningkatkan Pemahaman Penjumlahan Pecahan Siswa Sekolah Dasar - Imam Taufiq; Syafri Ahmad; Salmaini Salmaini (Lembaga Yasin AlSys, 2025)
Although ethnomathematics has been widely examined in previous research, studies that specifically integrate the traditional food getuk as a concrete medium in the development of Canva-based student worksheets (LKPD) for teaching fraction addition remain very limited. This study aims to develop and evaluate the effectiveness of Canva-based LKPD incorporating ethnomathematical representations of getuk in improving students’ ability to solve word problems involving fraction addition. A quantitative approach was employed using a 4-D Research and Development (R&D) design, involving 25 fifth-grade students selected through purposive sampling. Data were collected through classroom observations, expert validation, and formative tests, and were analyzed using the Wilcoxon Signed Rank Test and descriptive statistics. The results indicate that the developed LKPD falls into the “highly valid” category in terms of language, content, and visual design, and is effective in improving student learning outcomes, as evidenced by a Z value of –4.548 with p < 0.001. These findings reinforce constructivist and ethnomathematical theory by demonstrating that concrete experiences grounded in local cultural practices can facilitate deeper understanding of fraction concepts. The study concludes by underscoring the importance of integrating local cultural media into the development of contextual teaching materials, recommending the use of getuk as a concrete medium in fraction instruction, and opening avenues for further research employing stronger experimental designs and larger sample sizes.